microRNA-9 functions as a tumor suppressor in colorectal cancer by targeting CXCR4 - Xiong, Wan-Cheng (Int J Clin Exp Pathol, 2018)
MicroRNAs (miRs) dysregulation has been proven to play a crucial role in the initiation and progression of colorectal cancer (CRC). miR-9 functions as a tumor suppressor in many cancer types, including CRC. However, the precise role of miR-9 and the underlying molecular mechanisms that miR-9 involves in CRC progression remain largely unknown. In this study, it was reported that miR-9 had lower expression in CRC tissue samples than in those matched adjacent non-tumor tissues. Deregulated miR-9 expression was inverse correlated with the TNM stage, lymph node metastasis, and prognosis of CRC patients. Ectopic miR-9 expression suppressed CRC cell proliferation, migration, and invasion. Dual-Luciferase Reporter Assay confirmed that C-X-C Motif Chemokine Receptor 4 (CXCR4) was a direct miR-9 target, and the effects of miR-9 were mimicked through CXCR4 depletion in vitro. CXCR4 rescue experiments further verified that CXCR4 is a functional target of miR-9. Animal xenograft assays also provided evidence that miR-9 functions as a tumor suppressor via targeting CXCR4 in vivo. Mechanistically, miR-9 overexpression or CXCR4 knockdown influenced cell proliferation and epithelial-mesenchymal transition (EMT). Results suggest that miR-9 acts as a tumor suppressor in CRC progression by regulating CXCR4.